Association between endometriosis and arthritis: results from NHANES 1999-2006, genetic correlation analysis, and Mendelian randomization study - Xu, Huanying; Zou, Haoxi; Wen, Qidan; Xing, Xiaoyan; Xu, Ningning; Wu, Suzhen (Frontiers in Immunology, 2024)
Background: Previous studies reported that endometriosis may have a higher risk of arthritis. However, it remains unclear whether the association between endometriosis and arthritis has genetic correlations, or the relationship is causal. Linkage Disequilibrium Score (LDSC) and Mendelian Randomization (MR) analyses use genetic variation as a natural experiment to explore genetic correlations and causal inferences from observational data, reducing unmeasured confounding factors. Method: Participants (aged 20-54 years, n = 2,915) for the cross-sectional study were obtained from the National Health and Nutrition Examination Survey (NHANES).Endometriosis and arthritis were diagnosed based on self-reported by reproductive health and medical condition questionnaire. Weighted multivariable logistic regression was used to explore the relationship between endometriosis and arthritis. LDSC and MR analysis were performed using the genome-wide association study (GWAS) summary statistics to identify the causal association. Result: A significant positive association between endometriosis and arthritis was found after multivariable adjustment (OR = 1.89; 95% CI: 1.33, 2.67). When exploring different types of arthritis, a positive association was revealed with rheumatoid arthritis (RA), other types of arthritis, and cases that the arthritis type were unknown, with an OR of 2.07 (95% CI: 1.03, 4.17), 2.78 (95% CI: 1.30, 5.95), and 2.06 (95% CI: 1.36, 3.11), respectively. However, genetic correlation analysis between endometriosis and RA did not reveal any significant findings (all P values > 0.05). Moreover, MR analysis also failed to identify a causal relationship between endometriosis and RA (all P values > 0.05). Conclusion:Cross-sectional study identified a significant positive association between endometriosis and arthritis among US women, especially among RA, while findings based on LDSC and MR analysis did not support a genetic correlation or causal role.These findings suggest that clinicians should pay more attention to the coexistence of RA in endometriosis patients and explore the shared pathophysiological mechanisms of these two disorders, with a particular focus on extrinsic factors rather than intrinsic genetic inheritance.